Benefit of Endoscopic Surgery in the Management of Acute Invasive Skull Base Fungal Rhinosinusitis - D'Andrea, Megan R.; Gill, Corey M.; Umphlett, Melissa; Govindaraj, Satish; Del Signore, Anthony; Bederson, Joshua B.; Iloreta, Alfred M.C.; Shrivastava, Raj K. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective This article aims to characterize 14 patients who underwent purely endoscopic surgical debridement of acute invasive skull base fungal rhinosinusitis, and to evaluate postoperative outcomes and risk for recurrence.Design Retrospective cohort study.Setting Tertiary single-institution neurosurgery department.Participants We performed a retrospective analysis of all patients with skull base fungal infections treated with a purely endoscopic surgical approach at Mount Sinai Hospital from 1998 to 2018.Main Outcome Measures Clinical presentation, number of recurrences, and mortality rate.Results The most common underlying medical comorbidities were hematologic malignancy in 8 (57.1%) patients and poorly controlled diabetes mellitus in 7 (50%) patients. Presenting symptoms included headache (50%), eye pain (35.7%), facial pain (28.6%), visual changes (21.4%), and nasal congestion (14.3%). The fungal organisms identified on culture were Aspergillus (42.9%), Mucorales (28.6%), Fusarium (14.3%), Penicillium (7.1%), and unspecified (7.1%). Eight (57.1%) patients developed recurrence and required multiple surgical debridements. Patients who had only a hematologic malignancy were more likely to require multiple surgical debridements compared with those who did not have a hematologic malignancy or those who had both hematologic malignancy and underlying diabetes mellitus (p = 0.03). The mortality rate from surgery was 42.9%.Conclusion Surgical endoscopic intervention is an option for definitive management of acute invasive skull base fungal rhinosinusitis; however, postoperative mortality and risk of recurrence requiring additional surgical interventions remains high. Patients with hematologic malignancy may be more susceptible to recurrent infection requiring multiple surgical debridements. We recommend early aggressive multimodal treatment. Multiple debridements may be warranted in most cases; close clinical surveillance is needed during neurosurgical intervention.
Keywords: acute fungal rhinosinusitis; endoscopic surgery; skull base; Aspergillus; Mucorales